Paradigma Ilmu Agama, Sosial dan Humaniora - Muhammad Majduddin (Institut Keislaman Abdullah Faqih Gresik, 2018)
Abstract: This article discusses the paradigm of science by focusing on the paradigm of the religion, social and humanities. The discussion in this article is very importantbecause the development of science will continue to occur evolutionarily. The study carried out in this article is expected to contribute to the development of science in the life of mankind. The method used in this article is to conduct a study through the study of literature. Among the results of the study in this article are Religion and Science together designing and preparing for the future of humanity. Religious design is further and abstract and provides peace of life after death, while science and technology are shorter and concrete designs to deal with life in this world.Keyword: Paradigm, religion, social and humanities.